2012
DOI: 10.1186/1742-6405-9-35
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated sensory neuropathy in HIV-1 infected patients at the Douala General Hospital in Cameroon: a cross-sectional study

Abstract: BackgroundPeripheral neuropathy (PN) which is the most common neurological complication of HIV infection is under recognised and undertreated especially in resource limited settings. This ailment which has a negative impact on the quality of life of HIV/AIDS patients exists in different clinical patterns of which HIV-associated Sensory neuropathy (HIV-SN) is the most common affecting up to two thirds of patients with advanced disease in some settings. In Cameroon where HIV is a major public health problem, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
4
27
4
Order By: Relevance
“…Post-ART prevalence in resource-limited settings from previous studies has been estimated between 20 and 50% [13][14][15] but with a wide variation noted in a previous systematic review [15]. Thirteen percent of the DART trial population reported preexisting peripheral neuropathy at ART initiation, which is lower than the post-ART peripheral neuropathy prevalence from previous studies, which however highlights the importance of nondrug-based factors.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Post-ART prevalence in resource-limited settings from previous studies has been estimated between 20 and 50% [13][14][15] but with a wide variation noted in a previous systematic review [15]. Thirteen percent of the DART trial population reported preexisting peripheral neuropathy at ART initiation, which is lower than the post-ART peripheral neuropathy prevalence from previous studies, which however highlights the importance of nondrug-based factors.…”
Section: Discussionmentioning
confidence: 75%
“…However, these tools have been less frequently used in resource-limited settings. The few existing studies in sub-Saharan Africa have shown widely varying prevalence of 1-60% with HIV or ART-related peripheral neuropathy [7,[9][10][11][12][13][14][15]. The post-ART incidence rates for peripheral neuropathy were also not consistent across several studies, varying between 0.9 and 40 per 100 person-years in a review [15].…”
Section: Introductionmentioning
confidence: 96%
“…[13] We found that HIV-SN is more common among middle-age group patients, similar with findings in other studies. [20] These authors reported 21% prevalence of HIV neuropathy. [20] This suggests that some patients though asymptomatic, might have abnormal signs related to HIV-SN but do not meet the HIV-SN diagnostic criteria as per the BPNS tool.…”
Section: Discussionmentioning
confidence: 96%
“…[20] These authors reported 21% prevalence of HIV neuropathy. [20] This suggests that some patients though asymptomatic, might have abnormal signs related to HIV-SN but do not meet the HIV-SN diagnostic criteria as per the BPNS tool. Some authors considered this group as asymptomatic PN who perhaps represent those with early HIV-SN who are more likely to become symptomatic when challenged with HAART or other risks for PN.…”
Section: Discussionmentioning
confidence: 96%
“…Most estimates of the prevalence of HIV DSP in the cART-era range from 50%–60%, although prevalence as low as 21% has been reported 2,6,7. This variability can be in part attributed to the different definitions of HIV DSP, with some studies defining DSP as one clinical sign (ie, reduced ankle reflexes or reduced pinprick sensation or reduced vibration sensation in the feet), some requiring two clinical signs, and some using validated screening or diagnostic instruments 7,43,49.…”
Section: Epidemiology: Prevalence and Incidence Of Hiv Neuropathymentioning
confidence: 99%